An introduction to modern theories of economic growth - Jones, Hywel G. (London : Nelson, 1975)
The central purpose of the book is to make more easily accessible some of the principal arguments and results of the theories and models of economic growth that have occupied such a prominent place in the economic theorising of the post- war era.
Includes index.
Bibliography: p. 241-250.
obn 24/01/2019
Loans
Keywords: Economic development; Economic growth; Economic theory